Does a Common Genetic Event Exist for Familial Thyroid Cancer? Results from a Large Family with fnmtc - Silvia, Cantara; Margherita, Baldassarri; Carlotta, Marzocchi; Katia, Capitani; Sagnella, Alfonso; Laura, Valerio; Cantore, Anna; Ilaria, Meloni; Alessandra, Renieri; Marco, Capezzone (Archives of Clinical and Biomedical Research, 2024)
Background: Despite several efforts, the genetic susceptibility of familial non medullary thyroid cancer (FNMTC), has remained still elusive. Methods: We performed Whole Exome Sequencing (WES) in a large family with 9 available members, 6/9 (67%) affected by FNMTC. Results: We found two missense variants, with CADD score >20: the c.C1519A (p.Pro507Thr, rs773271544) in PRKC? gene and the c.G1019A (p.R340Q) in CCZ1B gene. These alterations were absent in healthy subjects (n=40) and in 30 sporadic thyroid cancer patients. The p.P507T was possibly pathogenetic by SIFT and PRKC? is implicated with MAPK activation by STRING. When we searched for this mutation in other families, we failed to confirm this genetic event as causative of cancer in other 20 FNMTC patients belonging to 8 kindred. Conclusions: We concluded that the PRKC? p.Pro507Thr possibly represents a private mutation even if other studies including large FNMTC family are needed to define the percentage of familial thyroid cancer cases due this alteration.